Pemanfaatan Limbah Plastik sebagai Produk Edukatif untuk Mendorong Sikap Kreatif Mahasiswa Pendidikan Biologi - Chania Pitrisia; Fitria Arifiyanti; Dinar Asri Haruming Wijaya (WISE Pendidikan Indonesia, 2025)
The increasing problem of plastic waste demands innovative solutions that integrate environmental and educational aspects, particularly in fostering creative attitudes among biology education students as future teachers. This study aims to explore the utilization of plastic waste as an educational product to encourage students’ creative attitudes, focusing on five indicators: curiosity, imagination, openness to diversity, risk-taking, and appreciation. A descriptive qualitative design was employed, involving 40 undergraduate biology education students enrolled in the Biology Learning Media Development course. Data were collected through classroom observations, semi-structured interviews, and document analysis of students’ educational products, and were analyzed using Miles and Huberman’s interactive model with source and method triangulation to ensure validity. The findings revealed that imagination (80–85%) and appreciation (85–90%) were the most dominant indicators, while curiosity and openness to diversity were categorized as high, and risk-taking was relatively low (60–68%). One of the most notable products was the ecobrick pillow, designed as a dual-function medium: a creative biology learning tool and a campaign for environmental awareness. These results highlight that project-based learning through plastic waste recycling not only produces innovative media but also enhances affective dimensions such as creativity, collaboration, and environmental literacy. The implication of this study emphasizes the need to integrate project-based recycling strategies into higher education curricula as a sustainable education model aligned with the frameworks of Outcome-Based Education (OBE) and Education for Sustainable Development (ESD).